A Study on the Influencing Factors of Mobile Digital Music Selection in Subhealthy People Based on Perceived Value Theory. (30th March 2021) - Jiang, Ming; Lin, Liming; Zhang, Weiguo; Zhuang, Weiqing; Jin, Minghui; Lin, Yi
Abstract : Background . The mode of combining mobile terminals and mobile digital music has gradually entered a bottleneck period while promoting the development of the mobile terminal industry. Proposing personalized solutions for specific groups of people including subhealthy people has become the current direction for the further long-term development of this mode. Understanding the influencing factors that affect subhealthy people's selection of mobile digital music is an urgent problem that needs to be solved in the development of personalized solutions. Objective . This article analyzes the influencing factors of the purchase intent to buy mobile digital music for subhealthy people and provides suggestions for mobile terminal vendors on how to design personalized solutions for this group of people. Methods . In order to achieve the above goals, this article constructs an influencing factor model based on the theory of perceived value, collects data by means of questionnaires, and uses the method of structural equations to verify the proposed model. Results . The results show that perceived quality, perceived price, social value, and emotional value all have a significant effect on users' purchase intention. Meanwhile, the conditional value and epistemic value have a negative moderating effect on the relationship between the social value and subhealthy people's digital music purchase intention but strengthen the positive relationship between the emotional value and subhealthy people's digital music purchase intention. Conclusions . The analysis shows that mobile terminal vendors should have their own unique attitudes and feelings when designing personalized mobile digital music solutions for subhealthy people, clarify their position, find strategies to improve the experience of subhealthy people, and win the reputation of subhealthy people. Let subhealthy people have a sense of belongingness.